Maintaining Epigenetic Inheritance During DNA Replication in Plants - Iglesias, Francisco M.; Cerdán, Pablo D. (Frontiers in Plant Science, 2016)
Biotic and abiotic stresses alter the pattern of gene expression in plants. Depending on the frequency and duration of stress events, the effects on the transcriptional state of genes are “remembered” temporally or transmitted to daughter cells and, in some instances, even to offspring (transgenerational epigenetic inheritance). This “memory” effect, which can be found even in the absence of the original stress, has an epigenetic basis, through molecular mechanisms that take place at the chromatin and DNA level but do not imply changes in the DNA sequence. Many epigenetic mechanisms have been described and involve covalent modifications on the DNA and histones, such as DNA methylation, histone acetylation and methylation, and RNAi dependent silencing mechanisms. Some of these chromatin modifications need to be stable through cell division in order to be truly epigenetic. During DNA replication, histones are recycled during the formation of the new nucleosomes and this process is tightly regulated. Perturbations to the DNA replication process and/or the recycling of histones lead to epigenetic changes. In this mini-review, we discuss recent evidence aimed at linking DNA replication process to epigenetic inheritance in plants.